Entrepreneurial Intention Among the University Students: Personality Traits that Matter - Cheah Chew Sze; Yeow Jian Ai; Yeo Sook Fern; Yeap Jomay (Research Synergy Foundation, 2021)
Within this research, we want to study if personality traits will be the significant predictors for entrepreneurial intention. Based on our literature surveys, which showed that personality traits are found significantly linked to entrepreneurial intention in developed countries, we want to focus on four personality traits: (1). self-efficacy, (2). needs for achievement, (3). locus of control, and (4). tolerance for risk. We collected the data from total of 200 university students in Malaysia through a self-administered questionnaire, and later analyzed using SEM PLS 3.0. We found that self-efficacy, locus of control, and tolerance for risk are indeed significant predictors, even though the need for achievement is not. Comparatively, a small sample size may lead to generalization issues, self-report bias, and cross-sectional design considered the main limitations of this study. We also revealed that tolerance for risk is the most influential factor in the entrepreneurial intention among university students. Thus, our finding contributes to the scholarly literature on entrepreneurship study in Malaysia, and provides some recommendation for universities to encourage and support entrepreneurship among students.